2019
DOI: 10.4236/as.2019.107073
|View full text |Cite
|
Sign up to set email alerts
|

How Do White LEDs’ Spectra Affect the Fresh Weight of Lettuce Grown under Artificial Lighting in a Plant Factory?—A Statistical Approach

Abstract: Monochromatic light-emitting diode lamps (LEDs), emitting red and blue lights, revolutionized crop production in closed-system plant factories with artificial lighting in the early 1990s. The LED industry developed broad-spectrum white-LEDs by 2010, and many types of white-LEDs for home and office uses are now available for plant factory entrepreneurs. This paper tries to clarify whether these white-LEDs can be used as effective light sources in plant factories by examining what types of spectrum distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…The fresh lettuce weight was equal to 64.9 g plant -1 . The results were consistent with [23], where the lettuce was cultivated under warm white and natural white LEDs under PPFD of 200±10 µmol m -2 s -1 , CO 2 is 1200 ppm. The results of lettuce fresh weight were about 63.5-97.9 g plant -1 .…”
Section: Evaluation Of the 'Green Oak Lettuce' Production Yieldsupporting
confidence: 89%
“…The fresh lettuce weight was equal to 64.9 g plant -1 . The results were consistent with [23], where the lettuce was cultivated under warm white and natural white LEDs under PPFD of 200±10 µmol m -2 s -1 , CO 2 is 1200 ppm. The results of lettuce fresh weight were about 63.5-97.9 g plant -1 .…”
Section: Evaluation Of the 'Green Oak Lettuce' Production Yieldsupporting
confidence: 89%
“…A typical PCW-LED comprises a blue-LED chip and phosphors of one or more types incorporated in the encapsulation resin, of which the phosphors convert partial blue-LED light into green or red light ( Cho et al, 2017). Some reports have described that PCW-LED light can enhance plant growth compared to BR-light ( Han et al, 2017;Lu et al, 2019;Nozue et al, 2018), even to BGR-light ( Saengtharatip et al, 2018). In addition, PCW-LEDs (blue-LED chip plus phosphors of one or more types) have been popularized rapidly for general lighting applications ( Han et al, 2017), of which the cost can be less than 20% of that of common red LEDs ( Kusuma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the respective performances of PCW-LEDs of several types in growing plants. Their results have demonstrated that the relative SPD of PCW-LED light can strongly affect dry weight ( Han et al, 2017;Lu et al, 2019;Nozue et al, 2018;Saengtharatip et al, 2018;Zou et al, 2020). The results also indicate that the relative SPD of PCW-LEDs should be selected carefully to maximize dry mass production.…”
Section: Introductionmentioning
confidence: 99%
“…A typical PCW-LED comprises a blue-LED chip and one or more types of phosphor incorporated in the encapsulation resin, of which the phosphors convert partial blue-LED light into green and/or red light [17]. Some reports have described that PCW-LED light can enhance plant growth compared to BR-light [16,18,19], even to BGR-light [11]. In addition, PCW-LEDs (blue-LED chip plus one or more types of phosphor) have been rapidly popularized for general lighting applications [16], of which the cost can be less than 20% of that of common red LEDs [20].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have compared the performance of PCW-LEDs of several types in growing plants; they have shown that the relative SPD of PCW-LED light can strongly affect dry mass production [11,18,19,21].…”
Section: Introductionmentioning
confidence: 99%